English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Ok, heres the exact copy and paste of the test question.
If y(x-1)=z then x=


y-z
z/y + 1
y(z-1)
z(y-1)
1-zy

2006-11-16 12:50:38 · 7 answers · asked by Belinda M 1 in Science & Mathematics Mathematics

7 answers

z/y+1
becasue when u distribute it is yx-y=z. Then u solve for y and it is x=z/y+y

yx-y=z
+y +y
_________
yx=z+y
/y /y
______
x=z/y+y

2006-11-16 13:21:02 · answer #1 · answered by Anonymous · 0 0

its z/y +1

2006-11-16 20:53:22 · answer #2 · answered by Rajkiran 3 · 0 0

z/y+1

2006-11-16 20:51:57 · answer #3 · answered by L 4 · 0 0

They are right, its z/y +1

2006-11-16 20:58:03 · answer #4 · answered by Sith Lord 13 2 · 0 0

y(x-1)=z
divide both sides by y, x-1=z/y
add 1 to both sides, x=z/y+1

2006-11-16 20:58:15 · answer #5 · answered by gracemary2168 1 · 1 0

using the ennie mennie miney theory I came up with z(y-1)

2006-11-16 20:59:50 · answer #6 · answered by Anonymous · 0 0

gracemary has done the best

2006-11-17 02:58:52 · answer #7 · answered by grandpa 4 · 0 0

fedest.com, questions and answers